2021
DOI: 10.3390/ijerph18073687
|View full text |Cite
|
Sign up to set email alerts
|

Proposing a TAM-SDT-Based Model to Examine the User Acceptance of Massively Multiplayer Online Games

Abstract: This study is focused on the massively multiplayer online games’ acceptance. In general, while specialized literature reveals that the online gaming industry has grown strongly in recent years, little evidence is identified on its user acceptance. In this manner, the present study is an attempt to fill this gap. Concretely, two aims are defined: (1) proposing an acceptance model to predict the continuance usage of massively multiplayer online games, and (2) knowing how this continuance usage encourages social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 74 publications
2
13
1
1
Order By: Relevance
“…Wang’s study [ 59 ] on social software pointed out that users’ perceived autonomy support influences their posting behavior through autonomy motivation. Many recent studies also indicate that the psychological needs of autonomy, competence, and relatedness have significant positive effects on the perceived ease of use and perceived usefulness of IT [ 60 , 61 , 62 , 63 , 64 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wang’s study [ 59 ] on social software pointed out that users’ perceived autonomy support influences their posting behavior through autonomy motivation. Many recent studies also indicate that the psychological needs of autonomy, competence, and relatedness have significant positive effects on the perceived ease of use and perceived usefulness of IT [ 60 , 61 , 62 , 63 , 64 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The TAM believes that if ease of use and usefulness (cognition dimension) can arouse individual attitudes about technology, then it can affect use intention [ 10 ]. Previous studies have confirmed this hypothesis to indicate the importance of the emotional factor in determining customer attitudes [ 26 , 27 , 28 ], such as hedonic feelings of satisfaction and enjoyment. This study retrieved relevant emotional literature and found that Russell’s [ 14 ] emotional model can represent almost all emotional responses, such as satisfaction, enjoyment, happiness, and excitement.…”
Section: Hypothesis Development and Literature Reviewmentioning
confidence: 67%
“…The present study proposes that attitudes toward fintech chatbots should be linked to cognition factors (usefulness and ease of use) and emotion (pleasure and arousal) because the attitudes in an information technology setting should include not only cognition-based factors but also emotion-based factors. Indeed, previous studies have confirmed this hypothesis, and attitudes toward information technology have been examined as an intermediary between emotion–intention links [ 26 , 27 , 28 ]. In addition, attitudes toward information technology have also been examined as a mediator between cognition–intention links in the information technology adoption model [ 8 , 9 , 10 ].…”
Section: Evaluation Proceduresmentioning
confidence: 75%
“…Since Davis et al (1989) developed the TAM theory, numerous studies have examined the linkage between (PU) and technology adoption in various sectors, such as health management tools (Liu et al, 2022), E-learning (Liao et al, 2022), online game (Linares et al, 2021), and financial technology or mobile payment (Ahmad et al, 2021;Nathan et al, 2022;Setiawan et al, 2021). PU is defined in this paper as the significance of new technology in improving user performance.…”
Section: Perceived Usefulness (Pu)mentioning
confidence: 99%